Enterprise Surveys : Iraq Country Profile 2011 - World Bank (Washington, DC, 2017)
The enterprise surveys focus on the many factors that shape the business environment. These factors can be accommodating or constraining for firms and play an important role in whether a country will prosper or not. An accommodating business environment is one that encourages firms to operate efficiently. Such conditions strengthen incentives for firms to innovate and to increase productivity-key factors for sustainable development. A more productive private sector, in turn, expands employment and contributes taxes necessary for public investment in health, education, and other services. In contrast, a poor business environment increases the obstacles to conducting business activities and decreases a country's prospects for reaching its potential in terms of employment, production, and welfare. The enterprise surveys are conducted by the World Bank and its partners across all geographic regions and cover small, medium, and large companies. The surveys are administered to a representative sample of firms in the non-agricultural formal private economy. The topics covered in enterprise surveys include infrastructure, trade, finance, regulations, taxes and business licensing, corruption, crime and informality, finance, innovation, labor, and perceptions about obstacles to doing business. The enterprise survey is useful for both policymakers and researchers. The surveys are repeated over time to track changes and benchmark the effects of reforms on firm performance.